Polymorphic variants of the PPAR (Peroxisome Proliferator-Activated Receptor) genes: relevancefor athletic performance - Maciejewska-Karłowska, Agnieszka (Akademia Wychowania Fizycznego w Poznaniu)
The elite athletic phenotype is a complex combination influenced by both multiple genes (polygenic) and environmental factors such as training and nutrition. Among single nucleotide polymorphisms (SNPs) associated with variation in physical traits, which are particularly important for performance in a variety of sports and with the elite athlete status, variants of PPAR (Peroxisome Proliferator-Activated Receptor) genes have emerged as crucial moderators that control the expression of genes encoding enzymes and other proteins involved in energy homeostasis (lipid and carbohydrate metabolism). Accumulated findings from studies showing that combinations of polymorphic markers located in PPAR genes are associated with increased/decreased performance raise the possibility that the PPAR gene variants are true performance enhancing polymorphisms (PEPs) that are believed to have a physiological impact on human body composition and metabolism. The aim of this review is to summarize the state of knowledge on the role of polymorphic variants of PPAR genes in physical performance or health related fitness phenotypes.
Keywords: PPARA; PPARG; PPARD; athletes; performance